Nonfragile stabilization for uncertain system with interval time‐varying delays via a new double integral inequality. (27th June 2018) - Samidurai, R.; Sriraman, R.; Cao, Jinde; Tu, Zhengwen
Abstract : In this paper, the problem of nonfragile stabilization for uncertain systems with interval time‐varying delays via new double integral inequality approach is studied. Based on the auxiliary function‐based integral inequality, a new double integral inequality is developed in this literature. Then, to prove the potency of the proposed inequality, some less conservative stability conditions are derived with the help of Lyapunov‐Krasovskii functional and linear matrix inequality technique. Three benchmark illustrative examples are delivered with simulations to validate the effectiveness and advantages of present results.